WORKING MEMORY TRAINING AS A TOOL FOR LANGUAGE LEARNING. (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: Learning a language depends heavily on working memory, a cognitive system necessary for processing and temporarily storing information. It makes things like learning new words, understanding sentences, digesting grammar, and communicating in real time easier. Working memory training has the potential to improve language learning outcomes by strengthening learners' ability to handle linguistic input, according to recent study. Strategies like chunking exercises, span tasks, and dual-N-back activities have demonstrated potential in improving sentence processing, memory retention, and fluency development. It is still up for dispute, though, whether these training effects translate to tasks that are peculiar to a given language. Although working memory training takes a lot of time and has varying effects on different people, adding customized activities to language curriculum may improve students' linguistic and cognitive skills. This study examines the connection between working memory and language acquisition, assesses training approaches, and talks about their usefulness and drawbacks.